Eloquent Exchange: Asceticism and Shirāʾ in the Poetry of Qaṭarī b. al-Fujāʾa - Gaiser, Adam R. (Rulers as Authors in the Islamic World Knowledge, Authority and Legitimacy, 2024)
Abstract The world-denying ethos of Qaṭarī b. al-Fujāʾa’s poetry and sermons seems in conflict with the more worldly implications of his leadership role as Caliph of the Azāriqa Khārijites. By clarifying what purposes his missives might have served in the contexts in which they appeared, and by asking how the Azāriqa might have conceptualized governance (as succession to the Prophet Muḥammad and as chief of a militarized conquest state), it will be shown that Ibn al-Fujāʾa and the Azraqīs idealized the austerity of the Muslim conquests (futūḥāt), while simultaneously looking to figures such as ʿUmar b. al-Khaṭṭāb as tacit models of exemplary guidance. His literary output and leadership role thus make sense when examined in their late antique context.
Keywords: poésie kharijite

From Sacrilege to Sacrifice. Observations on Violent Death in Classical and Modern Arabic Poetry - Neuwirth, Angelika (Martyrdom in Literature: Visions of Death and Meaningful Suffering in Europe and the Middle East from Antiquity to Modernity, 2004)
Keywords: poésie kharijite

Ask the battle of Qudayd: victory and identity in the Holy Cities - Higgins, Annie C. (Middle East Studies Association of North America (MESA) annual meeting, 2011)
Keywords: poésie kharijite

My father is Islam: Shurat poets redefining family ties - Higgins, Annie C. (Middle East Studies Association of North America (MESA) annual meeting, 2005)
Keywords: poésie kharijite

The Qur'anic Exchange of the Self in the Poetry of Shurāt (Khārijī) political identity 37-132 A.H./657-750 A.D. - Higgins, Annie C. (University of Chicago, 2001)
Keywords: poésie kharijite

Une poésie du combat: la poésie kharédjite - Sanagustin, Floréal (L'Orient au coeur: en l'honneur d'André Miquel, 2001)
Keywords: poésie kharijite

احسان عباس وتحقيق الشعر - بكار, يوسف حسين (جذور, 2000)
Keywords: poésie kharijite